2003
DOI: 10.1116/1.1541571
|View full text |Cite
|
Sign up to set email alerts
|

Influence of seed layers on microstructure and electrical properties of indium-tin oxide films

Abstract: Films of indium-tin oxide (ITO) were deposited by ion-beam sputtering. Two types of seed layers of ITO were deposited prior to bulk-layer deposition. The types of seed layers were determined by ion species, namely, either pure Ar+ or a mixture of Ar+ and O2+. The microstructure and the preferred orientation of the bulk films mimicked those of the seed layer. Films with larger grains were obtained when the seed layer was used. The electron mobility did not depend on the type of microstructure. The ability to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The most common polar surfaces are {001}, which can be either positively or negatively charged depending on the stacking and termination of Zn 2+ or O 2ions on the surfaces. It is also reported that the polycrystalline ITO film surface with random orientation is not atomically smooth 25 . Without the heat-treatment, the initial ZnO deposit would dissolve into the 0.015M aqueous solution for subsequent growth.…”
Section: Resultsmentioning
confidence: 99%
“…The most common polar surfaces are {001}, which can be either positively or negatively charged depending on the stacking and termination of Zn 2+ or O 2ions on the surfaces. It is also reported that the polycrystalline ITO film surface with random orientation is not atomically smooth 25 . Without the heat-treatment, the initial ZnO deposit would dissolve into the 0.015M aqueous solution for subsequent growth.…”
Section: Resultsmentioning
confidence: 99%
“…5d), are apparently determined by the first 15 nm thick layer acting as a template layer. According to our studies, the template layer determined the structural properties, such as crystallographic orientation, microstructure, and surface morphology of the entire ITO films [21,22]. However, the electrical properties of ITO films in Set 2 were dependent not on the template layer but on the bulk layer.…”
Section: Influence Of Seed Layer On Microstructure and Surface Morphomentioning
confidence: 91%